2015
DOI: 10.1039/c4tc01969e
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport in nanoparticular thin films of zinc oxide and aluminum-doped zinc oxide

Abstract: In this work, we report on the electrical characterization of nanoparticular thin films of zinc oxide (ZnO) and aluminum-doped ZnO (AZO). Temperature-dependent current-voltage measurements revealed that charge transport for both, ZnO and AZO, is well described by the Poole-Frenkel model and excellent agreement between the experimental data and the theoretical predictions is demonstrated. For the first time it is shown that the nature of the charge-transport is not affected by the doping of the nanoparticles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Printing the PbS nanocrystal ink described below in detail on top of the electrodes resulted in a catastrophic destruction of the silver electrodes (Figure S2). Thus, a protective layer of ZnO nanoparticles (N10-Nanograde) was printed on top of the electrode structure, including the silver fingers and the gap regions in between the fingers. As a side effect, the ZnO layer resulted in a reduced dark current due to its hole-blocking nature. , However, the ∼20 nm thick nanoparticle film did not decrease the current measured under white-light illumination, as was proven on lithographically prepared gold electrodes (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Printing the PbS nanocrystal ink described below in detail on top of the electrodes resulted in a catastrophic destruction of the silver electrodes (Figure S2). Thus, a protective layer of ZnO nanoparticles (N10-Nanograde) was printed on top of the electrode structure, including the silver fingers and the gap regions in between the fingers. As a side effect, the ZnO layer resulted in a reduced dark current due to its hole-blocking nature. , However, the ∼20 nm thick nanoparticle film did not decrease the current measured under white-light illumination, as was proven on lithographically prepared gold electrodes (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] Having overcome the ligand limitations, Lenz et al recently showed that the nature and the quality of the metal oxide determine the transport mechanism. [ 12 ] Defect-related energy levels or Poole-Frenkel defects wileyonlinelibrary.com not only control the transport but also may impact the interface formation. [ 12 ] Several strategies were developed to address these issues.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Defect-related energy levels or Poole-Frenkel defects wileyonlinelibrary.com not only control the transport but also may impact the interface formation. [ 12 ] Several strategies were developed to address these issues. Conjugated as well as nonconjugated polyelectrolyte interface modifi ers were shown to provide a simple and quite universal n-type interface to PCBM, which in the case of poly(imines) was hypothesized to lower the work function because of the orientation of positive charges at the contact/ active layer interface.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the TEM cross-sectional images of ZTO TFTs with and without the AZO nanoparticle layer incorporated. The nanoparticulate AZO layer is selected as the charge trapping medium because AZO nanoparticles contain substantial surface defects, 12 which can serve as charge trapping sites. By adding an AZO nanoparticle layer between AlO x and SiO 2 , the interface is apparently rumpled (Figure 1a), which indeed provides defect sites for charge trapping.…”
Section: Resultsmentioning
confidence: 99%